Biomarker discovery in galactosemia: Metabolomics with UPLC/HRMS in dried blood spots - Alodaib, Ahmad N.; Nimer, Refat M.; Alhumaidy, Rowan; Alhenaky, Alaa; Abdel Jabar, Mai; AlMalki, Reem H.; Abdel Rahman, Anas M. (Frontiers in Molecular Biosciences, 2023)
Galactosemia (GAL) is an autosomal recessive genetic disorder characterized by galactose metabolism disturbances. GAL develops non-preventable life-threatening complications even with a reduced content of galactose and lactose patient’s diet. Thus, the underlying pathophysiology of long-term complications in GAL remains poorly understood. In the current study, a metabolomics approach using ultra-performance liquid chromatography coupled with high-resolution mass spectrometry (UPLC/HRMS) was used to investigate the metabolomic changes in the dried blood spots of 15 patients with GAL and 39 healthy individuals. Compared to the control group, 2,819 metabolites underwent significant changes in patients with GAL. In all, 480 human endogenous metabolites were identified, of which 209 and 271 were upregulated and downregulated, respectively. PA (8:0/LTE4) and ganglioside GT1c (d18:0/20:0) metabolites showed the most significant differential between GAL and the healthy group, with an area under the curve of 1 and 0.995, respectively. Additionally, our findings showed novel potential biomarkers for GAL, such as 17-alpha-estradiol-3-glucuronide and 16-alpha-hydroxy DHEA 3-sulfatediphosphate. In conclusion, this metabolomics study deepened the understanding of the pathophysiology of GAL and presented metabolites that might serve as potential prognostic biomarkers to monitor the progression or support the clinical diagnosis of GAL.